Consensusability of discrete-time multi-agent systems via relative output feedback - You, Keyou (2011)
This paper investigates the joint effects of agent dynamic and network topology on the consensusability of linear discrete-time multi-agent systems via relative output feedback. An observer-based distributed control protocol is proposed. A necessary and sufficient condition for consensusability under this control protocol is given, which explicitly reveals how the intrinsic entropy rate of the agent dynamic and the eigenratio of the undirected communication graph affect consensusability. As a special case, the discrete-time double integrator system is discussed where a simple control protocol directly using the two-step relative position feedback is provided to reach a consensus. The theoretic results are illustrated by a simulation example.